Expression and contribution of microphthalmia-associated transcription factor to the melanin deposition in Liancheng white ducks - Qing-wu XIN; Zhong-wei MIAO; Zhao-yuan LIU; Li LI; Lin-li ZHANG; Zhi-ming ZHU; Zheng-hong ZHANG; Nen-zhu ZHENG; Zheng-chao WANG (Journal of Integrative Agriculture, 2020)
The present study investigates the expression of microphthalmia-associated transcription factor (MITF) and its contribution to the melanin deposition in Liancheng white ducks. Nested PCR was used to clone the MITF gene sequence from the skin tissue of female Liancheng white ducks. Ultraviolet spectrophotometry was used to detect the melanin deposition. MITF mRNA expression and melanin deposition in different tissues and organs were detected and their correlation was analyzed. The MITF gene (GenBank number: MG516570) was 1 323 bp in length, contains a complete CDS region (34–1 323 bp) and codes 429 amino acids with 100% homology to the MITF of Anas platyrhynchos and over 95% homology to those of Gallus gallus and Coturnix japonica. Genetic evolution analysis reveals a close relationship of Liancheng white ducks with A. platyrhynchos, and also to lesser extents with Anser cygnoides, silky fowl and G. gallus, as well as Sus scrofa, Ovis aries and other mammals. Real-time quantitative PCR (qPCR) analysis demonstrated that MITF was expressed in skin, gizzard, liver, kidney and muscle, and of these tissues, its expression was the highest in the skin tissue (skin>gizzard>liver>kidney>muscle). Ultraviolet spectrophotometry showed that melanin deposition was positively correlated with the MITF expression level in these five tissues and organs (P<0.05). Together, these results demonstrated a tissue-specific pattern of MITF expression and a positive correlation between MITF expression and melanin deposition, indicating that MITF expression may contribute to the melanin deposition in Liancheng white ducks.